An Analysis Of Angled-Corridor Effect On Pedestrian Walking Behaviour For Crowd Dynamics Simulations - Alias, Nur Aina (2019)
Corridor with angle or known as angled-corridor is one of the geometrical condition or facilities that could trigger restrictions to pedestrian flow and causing congestion during rush hour. There are a few factors that lead to the occurrence of congestion at the corridor, for instance, the degree of a corridor, track distance, density of the pedestrian, nature of direction flow, width of the corridor, building structure, and psychological effect. This thesis focuses on the effect of angled-corridor on pedestrian walking behaviour. This study was conducted with the aim to determine empirically the relationship between pedestrian velocity and density of pedestrian empirically unidirectional free flow by focusing the angled-corridors. Next, this study also aim to determine the threshold number of pedestrian and corresponding angled-corridor related to different number of pedestrian, beyond which the egress time can be decrease rapidly due to a strong degradations of congestion behaviour near the corner. Further from the two main objectives mentioned, the egress time were estimated by simulating hypothetical walking scenarios at the angled-corridor by considering two factors: (1) different number of pedestrian, and (2) different angle of corridor. There were two main parts involved in this study, which are the experimental work and simulation work. The experiment of pedestrian walking through three different built angled-corridor facilities (60°, 90°, and 135°) were conducted at Dewan Serbaguna, Engineering Campus, Universiti Sains Malaysia. Meanwhile, the simulation work of hypothetical egress scenario at angled-corridor was carried out based on different number of pedestrian and different angle of corridor. For the simulation work, MAYA software and Crowd Behaviour Simulator for Disaster Evacuation (CBS-DE) has been employed. From the obtained results, the average walking velocity of pedestrian was inversely proportional to the number of pedestrian. As the number of pedestrian traversing the angled-corridor increase, the amount of free space available becomes limited, hence the average walking velocity decrease due to the movement of individual is being restricted. This subsequently affects the travel time. Results obtained from simulation work were egress time and interaction force. It can be observed that almost all simulation in correspondence to angled-corridor 60° recorded the longest egress time, while angled-corridor 135° shows the least egress time. Also, noted that both results for inflexion points and repulsion effect had shown that the angled-corridor 60° had the highest number of inflexion points and repulsion effect compared to the other angled-corridor. This indicate that corridor with angle less than 90° should be avoid while designing angled-corridor as it explicitly increase the egress time. The results obtain from this research are expected to be a useful database and tool for designing and dimensioning of future pedestrian facilities which involves corridor with varying angles and shape. In the future, this study should be further continue by considering more varied and detailed scenarios associated with turning movement at more different angled corridor.